PENGARUH SELF-LEADERSHIP, TIME MANAGEMENT DAN DIGITAL LITERACY TERHADAP PRESTASI BELAJAR MAHASISWA - Maemunah, Maemunah; Agustina, Tri Siwi; Ekowati, Dian (PT Naureen Digital Education, 2024)
Student learning achievement is a very important thing that must be considered. Of course, there are many factors that can influence student learning achievement, but this research will specifically discuss the role of self-leadership, time management and digital literacy. This research was conducted to find out how these factors influence the learning achievement of students at the Faculty of Medicine, Airlangga University. The method used in this research is quantitative with a simple random sampling technique. The population in this study were all students from the Faculty of Medicine, Airlangga University with a sample size of 120 students. Data collection was carried out by distributing questionnaires online. Data processing uses SPSS with multiple linear regression analysis. The results of this research show that self-leadership, time management and digital literacy both partially and simultaneously have a positive and significant effect on the learning achievement of students at the Faculty of Medicine, Airlangga University